2001
DOI: 10.1074/jbc.m102946200
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution and Molecular Analysis of the hRad9-hHus1-hRad1 (9-1-1) DNA Damage Responsive Checkpoint Complex

Abstract: DNA damage activates cell cycle checkpoint signaling pathways that coordinate cell cycle arrest and DNA repair. Three of the proteins involved in checkpoint signaling, Rad1, Hus1, and Rad9, have been shown to interact by immunoprecipitation and yeast two-hybrid studies. However, it is not known how these proteins interact and assemble into a complex. In the present study we demonstrated that in human cells all the hRad9 and hHus1 and approximately one-half of the cellular pool of hRad1 interacted as a stable, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
85
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 41 publications
(56 reference statements)
9
85
3
Order By: Relevance
“…We found that hHus1 was relatively unstable when compared to its close family members hRad1 and hRad9 in cells. The hRad1 protein is a stable molecule and its expression is not affected by hRad9 and hHus1, consistent with the findings that a large proportion of hRad1 can exist as a monomer in cells (Burtelow et al, 2001). The stability of hHus1 expression depends upon the presence of hRad1 but not hRad9, implying that hHus1 and hRad1 may form an ordered complex prior to the association hHus1-hRad9 for the formation of the hRad9-hRad1-hHus1 checkpoint complex.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We found that hHus1 was relatively unstable when compared to its close family members hRad1 and hRad9 in cells. The hRad1 protein is a stable molecule and its expression is not affected by hRad9 and hHus1, consistent with the findings that a large proportion of hRad1 can exist as a monomer in cells (Burtelow et al, 2001). The stability of hHus1 expression depends upon the presence of hRad1 but not hRad9, implying that hHus1 and hRad1 may form an ordered complex prior to the association hHus1-hRad9 for the formation of the hRad9-hRad1-hHus1 checkpoint complex.…”
Section: Discussionsupporting
confidence: 82%
“…It has been reported that the N-terminus of hHus1 interacts with the C-terminus of hRad9 (Burtelow et al, 2001). Therefore, it is possible that the failure of hRad9 to stabilize Myc-hHus1 is due to the c-Myc tag presented in the N-terminus of hHus1 that interferes with the association between hHus1 and hRad9.…”
Section: Stabilization Of Hhus1 Expression By Hrad1 But Not Hrad9mentioning
confidence: 99%
“…Another target for ATM and ATR phosphorylation in S phase is the 9-1-1 complex (Thelen et al, 1999;Burtelow et al, 2001;Lindsey-Boltz et al, 2001). Both the 9-1-1 complex and PIKKs are required for CHK1 activation in fission yeast in response to IR (Brondello et al, 1999).…”
Section: Signal Transduction Pathways Regulating Dsb Repairmentioning
confidence: 99%
“…The early genes in the pathway, which include Rad1, Rad3, Rad9, Rad17, Rad26 and Hus1, are thought to sense the DNA damage and lead to phosphorylation of the Chk1 protein [11]. In response to double strand DNA breaks (DSBs) induced by ionizing radiation, for example, Rad17 acts as a checkpoint-specific loading factor, which responds to the DNA damage by loading a 9-1-1 protein complex onto the sites where DNA is damaged [12,13]. The 9-1-1 protein com-plex is also known as the checkpoint clamp complex (CCC), which is composed of Rad1, Rad9 and Hus1 [13].…”
Section: Cell Cycle G2/m Controls and Check-pointsmentioning
confidence: 99%